How to approach and take care of minor adolescents whose situations raise ethical dilemmas? a position paper of the European academy of pediatrics - Michaud, Pierre-André; Takeuchi, Yusuke-Leo; Mazur, Artur; Hadjipanayis, Adamos A.; Ambresin, Anne-Emmanuelle (Frontiers in Pediatrics, 2023)
In the care of adolescents, health care providers often face situations raising ethical concerns or dilemmas, such as refusal of a treatment or hospitalization, or request of confidentiality while engaging in risky behaviors or facing unplanned pregnancy. This position paper provides concrete avenues as how to assess the adolescent’s capacity for autonomous decision making, e.g. the patient’s competence in a specific situation, and how to elicit informed choice or consent. To do so, professionals need to be sensitized and trained as how to assess the cognitive and socio-psychological development of the young patient. Another challenge for the health professionals is to balance the needs to support patient’s autonomy while offering secure guidance and protection if needed. To optimize such a process, they establish a climate of trust and empathy that will allow the patient to participate freely in the decision. In addition, especially when the decisions have potentially important consequences on the health and life, the professionals include, with the adolescent’s permission, parents, caregivers or other significant adults, as well as they may request the opinion of other members of the health care team or expert colleagues such as ethicists.